The Use of Asynchronous Google Classroom with Video Teaching Tutorial on Improving Student Writing Achievement for Recount Text at Public Senior High School 6 Kendari - Nggawu, La Ode; Alam, R. (PT Mattawang Mediatama Solution, 2022)
This study aims to investigate how effective asynchronous Google classroom with VTT on improving students' writing achievement for recount text at SMAN 6 Kendari used quantitative design with pre-experimental one group pre-test and post-test. The research population was 346 entire school who registered in academic year 2020/2021. Meanwhile, XI MIPA 3 were 28 students as a valid sample of this study. Sampling selected using simple cluster random. Data collection used a written test that analyst by paired sample t-test that shows descriptive and inferential statistics based on students pre-and post-test. The research finding shows that there was significant different in gain score for pre-test (M=62,50; SD= 5.853) and Post-test (M=80.1071; SD=5.09422), t (27) = 13.095; p < 0.05, ttable= 2.052. It shows t-count > t-table with sig α < 0.05, H0 is rejected and H1 is accepted, so it can be concluded that using asynchronous google classroom with video teaching tutorial show a positive effect on student writing achievement for recount text at SMAN 6 Kendari.